Intra-diploic epidermoid cyst: An iceberg lesion - Punia, Prashant; Chugh, Ashish; Gotecha, Sarang (Nepal Journal of Neuroscience, 2021)
Introduction: Intraosseous epithelial inclusion cysts of the skull, presenting as lytic defects, constitute a very small percentage of the primary intracranial tumours. The case is presented by virtue of not only the rarity of the variant but also to highlight the importance of timely intervention by a neurosurgeon after adequate investigation and in a tertiary care setting. Case Report: A 45 year old female patient presented to the local Primary Healthcare Centre(PHC) with a small scalp swelling in the occipital region. . Intraoperative identification of intracranial extension was made by the surgeon as inferior margin of the swelling couldn’t be reached and also by palpation of the huge bone defect following which the procedure was abandoned midway and patient was referred to our centre for further management. Imaging: Contrast Enhanced Computerised Tomograhy(CECT) revealed a well defined, mixed density lesion with hypodense and an isodense component in right occipital region. Lesion was measuring 4.2(Cranio caudal) x 3.3(Antero posterior) x 3.6( transverse) cm. A sharp marginated bone defect was noted involving both the outer and inner tables of the occipital bone. Operative management: Lesion was approached through a right occipital craniotomy wherein the margins of bone defect were nibbled away to gain a wide access to the lesion. Pearly white, flaky contents of the lesion along with capsule were identified and excised completely. Discussuion: Intradiploic epidermoid cysts are very rare, accounting for <3% of all intracranial epidermoid cysts.(5) These cysts grow very slowly and usually present as painless bony swelling under the scalp. Conclusion: Cranial epidermoid is a fairly common entity and intradiploic variant of the same isnot uncommonly seen in neurosurgical practise. These lesions may present as a small scalp lesion which should not be judged based on its apparent size as these lesions are not infrequently known to have a bigger intracranial extension